Protective action of Ampelopsis cantoniensis and its major constituent myricetin against LDL oxidation - Ha, Do Thi; Thuong, Phuong Thien; Thuan, Nguyen Duy (Vietnam Journal of Chemistry, 2014)
It is widely accepted that oxidative modification of lowdensity lipoprotein (LDL) plays a pivotal role in the initiation and development of atherosclerosis. In the present study, we found that the MeOH and H2O extracts of the plant Ampelopsis cantoniensis, and its main constituent, myricetin, possessed significant protective effects on LDL oxidation induced by either a metal ion (Cu2+) or a free radical (AAPH). All of these (MeOH ex., H2O ex., and myricetin) exhibited higher antioxidant activity than that of α-tocopherol in a dose dependent manner, and especially, myricetin disclosed stronger inhibitory effect than that of (+)-catechin, a major component of green tea. The result suggests that the decoction of the medicinal plant “che day” could be used beneficially as a remedy to prevent the LDL oxidation involved in the atherosclerotic lesion.